Penerapan Software Testing Life Cycle Pada Pengujian Otomatisasi Platform Dzikra - Ruliansyah, Ruliansyah; Tukino; Baenil Huda; April Lia Hananto (CSRID (Computer Science Research and Its Development Journal), 2023)
PT Bejana Investidata Globalindo (BIGIO), as an IT consultant and software development company, develops an in-house product called Dzikra which is a platform to help users build good habits in worship. In order to develop this system, the company requires a daily worship content management system known as the Dzikra web admin. The Software Development Life Cycle (SDLC) has several stages, one of the important stages is the testing stage which has the goal of evaluating whether the software has been created in accordance with the specifications and detects bugs or errors. Black box testing automation with Robot Framework can provide good testing documentation and can reduce human errors during the testing process. The implementation of the Software Testing Life Cycle (STLC) in the testing process can also make the testing flow more structured and provide a better focus on each testing stage. The results of the testing show that of the six features tested, they have run as expected. It is hoped that this research will provide support to PT Bejana Investidata Globalindo (BIGIO) in automating software testing process.